Identification of Breast Cancer Inhibitors Specific for G Protein‐Coupled Estrogen Receptor (GPER)‐Expressing Cells. (20th June 2017) - Aiello, Francesca; Carullo, Gabriele; Giordano, Francesca; Spina, Elena; Nigro, Alessandra; Garofalo, Antonio; Tassini, Sabrina; Costantino, Gabriele; Vincetti, Paolo; Bruno, Agostino; Radi, Marco
Abstract: Together with estrogen receptors ERα and ERβ, the G protein‐coupled estrogen receptor (GPER) mediates important pathophysiological signaling pathways induced by estrogens and is currently regarded as a promising target for ER‐negative (ER−) and triple‐negative (TN) breast cancer. Only a few selective GPER modulators have been reported to date, and their use in cancer cell lines has often led to contradictory results. Herein we report the application of virtual screening and cell‐based studies for the identification of new chemical scaffolds with a specific antiproliferative effect against GPER‐expressing breast cancer cell lines. Out of the four different scaffolds identified, 8‐chloro‐4‐(4‐chlorophenyl)pyrrolo[1, 2‐ a ]quinoxaline14 c was found to be the most promising compound able to induce: 1) antiproliferative activity in GPER‐expressing cell lines (MCF7 and SKBR3), similarly to G15; 2) no effect on cells that do not express GPER (HEK293); 3) a decrease in cyclin D1 expression; and 4) a sustained induction of cell‐cycle negative regulators p53 and p21. Abstract : Positive news for ER‐negative : We show how the combination of virtual screening on a GPER model and cell‐based assays quickly leads to the identification of new chemical entities that induce a specific antiproliferative effect on GPER‐expressing cells (MCF7 and SKBR3), but that have no effect on cells that do not express GPER. Further in vitro studies allowed identification of pyrrolo[1, 2‐ a ]quinoxaline14 c as the most interesting compound for hit‐to‐lead optimization aimed at developing new drugs to treat breast cancer.